Clinical and Laboratory Features of Covid-19 in Population of the Aral Sea Region - Seiytnazarova, A.; Kunnazarova, Z.; Karimova, G.; Abdirashitova, G.; Jaybergenova, J. (Asian Pacific Journal of Environment and Cancer, 2021)
The article summarizes the results of a study of a new coronovirus infection and their clinical and laboratory features of the course among patients in the southern Aral Sea region. Anamnestic, general clinical, laboratory-instrumental, statistical, diagnostic-visual and analytical research methods were used. An analysis was made of 97 case histories of patients aged 21 to 83 who were hospitalized in a repurposed hospital for the treatment of patients with coronavirus infection, located in Nukus (Republic of Karakalpakstan), during the period of the maximum peak of the epidemic (from September to November 2020 ). The prevalence of middle-aged and elderly patients with severe pneumonia (79%), cough - 76.3% and shortness of breath - 69.1% of cases; the disease was accompanied in 58% of cases by an increase in temperature and in 72.2% of cases by a decrease in the level of oxygen in the blood; increase in ESR, glucose, C-reactive protein; also a positive PCR test for coronovirus infection. The data of clinical laboratory and instrumental studies, the detection of COVID-19 inflammation biomarkers indicated damage to the lung tissue